Pengimplementasian Kurikulum Merdeka Dalam Pembelajaran Pendidikan Jasmani di MI Al-Hadi II - Sari, Kartika; Kurniawati, Wahyu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
Education is one of the needs for humans to continue developing. The development aims to achieve a better life in the future. Physical education is also a part of education. This research aims to understand the implementation of the Merdeka Curriculum in the Physical Education subject at MI Al-Hadi II. The research method used includes observation, documentation, and interviews with the school principal and related subject teachers. The approach used in this research is a qualitative approach to describe the reality of the events being studied, which is the implementation of the Merdeka Curriculum in the execution of physical education at MI Al-Hadi II. The results obtained from this research indicate that the implementation of the Merdeka Curriculum in Physical Education at MI Al-Hadi II is carried out freely by teachers but still within the control of the curriculum framework set by the government. With the Merdeka Curriculum, students can freely explore their abilities, especially in the field of sports, while still achieving the learning objectives.